Introduction to RNA‐Seq and its Applications to Drug Discovery and Development - Zainab Khatoon; Bryan Figler; Hui Zhang; Feng Cheng (2014)
Abstract Preclinical Research RNA sequencing ( RNA ‐ Seq ) is a novel high‐throughput technology for comprehensive transcriptome study. It can measure the expression levels of thousands of genes simultaneously and provide insight into functional pathways and regulations in biological processes. In addition, RNA ‐Seq can provide copious information on alternative splicing, allele‐specific expression, unannotated exons, and novel transcripts (gene or noncoding RNAs ). This technology has revolutionized the way biologists examine transcriptomes and has been successfully applied in drug discovery and development, being able to identify drug‐related genes, microRNAs , and fusion proteins. In this overview, we will review this technology including data analysis, and its recent applications in drug discovery and development.